Analysis Of The Causes Of JKN KIS Contribution Payment Arrears In The Working Area Of Kendari City "Study At The Abeli Public Health" - ikhsan, muhammad ikhsan akbar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2019)
Health Security Agency establishes the obligation to pay dues that must be followed in order to get health insurance society. But over time many participants BPJS is delinquent paying his dues BPJS. In June 2018 there were 711 souls who are still in arrears dues BPJS. This study aims to determine the factors associated with health BPJS arrears dues payments Independent in Puskesmas Abeli ??Kendari. This research is an analytic study with cross sectional study. The population is all participants are in arrears in the health center BPJS Abeli ??Kendari as 711. Total sample of 88 respondents. This study using Chi-square test. The results of statistical tests at the significance level ? = 0.05, the result is no strong enough relationship between knowledge and dues payment arrears BPJS (p-value = 0.000), there is a strong enough correlation between income with payment arrears dues BPJS (p Value-= 0.000), there is a strong enough correlation between the perception of the arrears payment of dues BPJS (p-value = 0.000). The conclusion showed that the non-payment of dues BPJS in touch with all the variables. By him that suggested need for socialization of the BPJS that participants understand more about BPJS resulting in the payment of contributions of participants BPJS not delinquent.